Key discursive themes for the environmental governance of the Vouga Estuary (Ria de Aveiro) - Sumares, David (2013)
Over the past decades, at the same time that traditional activities declined, the Ria de Aveiro (the estuary of the river Vouga) has suffered strong development pressures (urban, agricultural and industrial), which have caused severe environmental problems such as water pollution, eutrophication, habitat destruction, among others. In particular, changes in the estuary’s hydrodynamics are being increasingly seen as especially damaging to the Ria’s ecosystems, protected under the Natura 2000 Network. The dispersion of decision-making across 10 municipalities and various entities that have overlapping jurisdictions over the area has led to constant difficulties in finding coherent and articulated management solutions for the estuary’s ecosystem as a whole. The Polis Coastline Programme — a governmental initiative of “integrated redevelopment and enhancement operations” in coastal areas — intended to address some of Ria’s most urgent problems with an integrated “requalification” strategy. However, as it becomes evident from the opinions submitted during the consultations carried out in the context of the respective Strategic Environmental Assessment (SEA), the concrete meaning of sustainability in this complex semi-natural system is far from consensual among the different participants, and is often in tension with the vision behind the planned interventions. In particular, the role that the port is seen to occupy in a sustainable future constitutes an important focus of dispute. In this paper, based on the analysis of written opinions submitted during the SEA consultations, we point out to key-themes in local discourses that dialectically interrelate in ways which ought to be considered by this territory’s environmental governance.